2018
DOI: 10.1111/jocn.14304
|View full text |Cite
|
Sign up to set email alerts
|

A study on the information–motivation–behavioural skills model among Chinese adults with peritoneal dialysis

Abstract: The findings suggest that self-care education programmes for peritoneal dialysis patients should include strategies based on the information-motivation-behavioural model to enhance knowledge, motivation and behaviour skills to change or maintain self-care behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…However, on self-efficacy and self-management were reported differently in previous studies. Previous studies of self-management based on the IMB model in patients undergoing peritoneal dialysis (Chang et al, 2018) and stroke patients (Kim et al, 2022) showed that knowledge directly affected self-efficacy and self-management.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, on self-efficacy and self-management were reported differently in previous studies. Previous studies of self-management based on the IMB model in patients undergoing peritoneal dialysis (Chang et al, 2018) and stroke patients (Kim et al, 2022) showed that knowledge directly affected self-efficacy and self-management.…”
Section: Discussionmentioning
confidence: 98%
“…Motivation is the second element of the IMB model, and comprises personal and social motivation (Fisher & Fisher, 1992). Personal motivation involves individuals' attitudes towards health behaviour (Fisher & Fisher, 1992), and attitude was measured as personal motivation in previous studies (Chang et al, 2018; Kim et al, 2022). Therefore, we set an attitude towards COPD self‐management as personal motivation in this study.…”
Section: Introductionmentioning
confidence: 99%
“…An individual needs to possess the necessary skills to engage in certain behaviors, in both the health and security domain (see also [20,23,30]). However, there are mixed views on how behavioral skills can be measured, which led some authors to use self-efficacy measures to assess perceived capabilities to deal with challenges ( [18,[31][32][33]). An example here is the use of selfefficacy as a proxy measure for behavioral skills in terms of patients' health-related behavior (see work by Fisher and Fisher [16,21]).…”
Section: Fig 1 the Information-motivation-behavioral Skills Model And...mentioning
confidence: 99%
“…This model has been increasingly used in studies with various populations in intercultural settings. These studies draw attention to self-management for successful behavioral changes and emphasize that interventions that improve self-management will improve health outcomes (Chang et al, 2018; Cooperman, Lu, Richter, Bernstein, & Williams, 2018; Nelson et al, 2018; Zinatsa, Engelbrecht, van Rensburg, & Kigozi, 2018). Detection of the IMB model components enables the development of individualized interventions, which may increase self-efficacy, decrease negative attitudes, and cause a significant increase in the development of positive behavior at a higher level compared with traditional knowledge-based interventions (Yılmazer & Tuzer, 2017).…”
Section: Introductionmentioning
confidence: 99%